2020
DOI: 10.3390/cancers12051124
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Two Independent DNA and RNA Tissue-Based Multiplex Assays for the Routine Care of Advanced NSCLC Patients

Abstract: Personalized medicine is nowadays a paradigm in lung cancer management, offering important benefits to patients. This study aimed to test the feasibility and utility of embedding two multiplexed genomic platforms as the routine workup of advanced non-squamous non-small cell lung cancer (NSCLC) patients. Two parallel multiplexed approaches were performed based on DNA sequencing and direct digital detection of RNA with nCounter® technology to evaluate gene mutations and fusions. The results were used to guide ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…For controversial cases, a consensus was reached over a double headed microscope. References [ 18 , 20 , 21 , 22 , 23 ] are cited in the supplementary material .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For controversial cases, a consensus was reached over a double headed microscope. References [ 18 , 20 , 21 , 22 , 23 ] are cited in the supplementary material .…”
Section: Methodsmentioning
confidence: 99%
“…This situation prompted us to investigate the yield of EBUS-TBNA specimens, a cytological methodology, using a comprehensive multiplex genotyping based on combined next-generation sequencing (NGS) (DNA) and nCounter (RNA) multiplex testing [ 18 ], as well as PD-L1, in a series of patients with newly diagnosed NSCLC at our institution. We also aimed to assess the reproducibility of results between cytological specimens and paired tissue biopsies taken from the same tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiplexed panels for the detection of mutations and fusions in the lung cancer clinical environment has been exponentially increasing over the last few years [ 10 , 13 ]. Previous studies have shown that cytological smears and cell blocks are suitable for performing DNA and RNA massive sequencing [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the use of nCounter for simultaneous detection of fusions in ALK, ROS1, and RET [ 9 , 10 ] and, more recently, for MET alterations [ 11 ]. In this article, we analyze the prospective use of the nCounter technology for the detection of fusions, MET Δ ex14 splicing and MET very high expression in NSCLC cytological samples and we compare the results with FFPE biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…The NanoString nCounter™ Analysis System is a high-throughput, quantitative transcript-based hybridization technology that allows for the simultaneous analysis of the expression of hundreds of target genes [26] and can be easily incorporated in the routine molecular testing workflow of tumor samples [27].…”
Section: Introductionmentioning
confidence: 99%